Anti-Inflammatory Interleukin 10 Inversely Relates to Coronary Atherosclerosis in Persons With Human Immunodeficiency Virus. (11th May 2019) - Fourman, Lindsay T; Saylor, Charles F; Cheru, Lediya; Fitch, Kathleen; Looby, Sara; Keller, Kiana; Robinson, Jake A; Hoffmann, Udo; Lu, Michael T; Burdo, Tricia; Lo, Janet
Abstract: Interleukin 10 (IL-10) is an anti-inflammatory cytokine that may be protective against coronary atherosclerosis. In an observational study of persons with human immunodeficiency virus (PWH) and uninfected controls, IL-10 was measured in serum samples by means of enzyme-linked immunosorbent assay, and coronary atherosclerosis was assessed using computed tomographic angiography. Among PWH, a 10-fold decrease in IL-10 was associated with a 2.6-fold increase in the odds of coronary plaque ( P = .01), after controlling for traditional and nontraditional cardiovascular risk factors. IL-10 was also inversely associated with total coronary plaque (ρ = −0.19; P = .02) and noncalcified coronary plaque (ρ = −0.24; P = .004). Our findings suggest a role for IL-10 in mitigating atherosclerosis in PWH. Clinical Trials Registration . NCT00455793 Abstract : Immune factors that may be atheroprotective in human immunodeficiency virus (HIV) have not been well identified. Our observational study showed an inverse association between anti-inflammatory interleukin 10 and coronary plaque, suggesting that interleukin 10 may help mitigate atherosclerosis in HIV.